Comportamento do papagaio-do-mangue Amazona amazonica: gregarismo, ciclos nictemerais e comunicação sonora - MOURA, Leiliany Negrão de (2007)
In this study we carried through the Orange-winged-parrot Amazona amazonica census in a roosting site, the Parrots Island, located next to Belém, Pará. With the countings we verify that the total number of parrots, the number of isolated individuals, couples, groups of three, four and five individuals presented a fluctuation, indicating reproductive seasonality, that influences in the number of individuals with the reduction of its participation in the groups that sleep in the island during its reproductive period, since the species supplies parental cares to the offsprings. In relation to the nychtemeral cycle, we evaluate the influence of abiotic factors in the schedules of displacements of the individuals of this population in the roosting site. We establish a form to register the frequency of its arrival or exit from minute to minute and relate the data gotten with the sunset and sunrise schedules. We verify that the percentage average of individuals that arrives and leaves is significantly greater after sunset and before sunrise, respectively, and that adverse weathers conditions influence significantly in the daily movement of the parrots, masking the real positioning of the Sun, advancing or delaying its arrival and exit of the roosting site. Although the Orange-winged-parrot is a diurnal avian, they dislocate in schedules of low luminosity, being the photoperiodism a entrainment agent of its activities. About its acoustic communication, it presents 9 vocalizations in the vocal repertoire during the reproductive period, related to three different behavior categories. Moreover, it exists an individual difference in its flight contact call and populational dialects between the studied populations.